Performance enhancement of S-band thulium doped fiber laser using 800NM and 1800NMB and supressed ASE - Lee H.J.; Soofi M.G.; Arabanian A.S.; Emami S.D. (Nova Science Publishers, Inc., 2023)
Aluminum; Amplifiers (electronic); Chromium compounds; Crystal whiskers; Fiber lasers; Noise figure; Nonlinear optics; Optical fiber communication; Optical fibers; Photonic crystal fibers; Thulium; Amplified spontaneous emissions; Distribution profiles; Noise figure improvement; Performance enhancements; TDFA; Thulium doped fiber amplifiers; Thulium-doped fibers; Wavelength regions; Erbium doped fiber amplifiers